The Relationship between Health Literacy and Covid-19 Preventive Behaviors in Healthcare Workers in Sistan and Baluchistan Province, Southeast Iran - Hossien Izadirad; Hossein Rashki Ghalenow; Hajar Noori Sanchooli; Fereshteh Safaei (Shiraz University of Medical Sciences, 2023)
Background: Health literacy and preventive behaviors can be considered important factors in healthcare workers' decisions and how they function in the health system to promote the health of society. Therefore, the present study determined the relationship between health literacy and Covid-19 preventive behaviors among healthcare workers in Sistan and Baluchestan province, southeast Iran.Methods: This descriptive-analytical (cross-sectional) study was conducted on 300 healthcare workers in Sistan and Baluchistan province in 2021. Samples were collected by convenience method through social media. Data were collected electronically using the Health Literacy and Covid-19 preventive behaviors questionnaire. Data were analyzed by frequency, mean, Pearson correlation coefficient, and linear regression.Results: Only 24.4% of healthcare workers had sufficient health literacy. The healthcare workers' health literacy mean score was 58.39±8.57 out of 88. Also, the score of health literacy in the dimension of access was 16.38±3.45, in the dimension of understanding was 17.06±3.74, in the dimension of appraisal was 14.28±3.40, and in the dimension of the use of health information was 13.74±2.93. The mean score of preventive behaviors was 30.54±6.16 out of 48. A positive and significant relationship was observed between health literacy and preventive behaviors. Demographic variables predicted 29% of the variance of Covid- 19 preventive behaviors, with health literacy being the strongest predictor (β=0.225).Conclusion: The results of this study confirmed the predictive role of health literacy in Covid-19 preventive behaviors. Also, poor and borderline health literacy concerning Covid-19 was a common problem among healthcare workers in Sistan and Baluchistan province, so it reduced the probability of performing Covid-19 preventive behaviors. Therefore, it is essential to design and implement interventions to improve the health literacy of healthcare workers.